FACTORS INFLUENCING THE FORMATION OF IQBOL MIRZO’S ARTISTIC CREATIVITY (Scientific journal of the Fergana State University, 2026)
The article identifies and analyzes the key factors that contributed to the formation of the creative mastery of Iqbol Mirzo, People’s Poet of Uzbekistan. The influence of oral folk literature, Uzbek classical literature, and world literature, as well as the expression of national identity, the distinctive structure of stanza and rhyme, are shown to play a significant role in shaping the originality of the poet’s work.